Application of single and multi-solid phase STFs to Twaron fabrics: evaluation of energy absorption performances - Yanen, Cenk; Solmaz, Murat Yavuz; Aydogmus, Ercan (Taylor & Francis Ltd, 2024)
The present study aims to enhance the energy absorption performance of Twaron aramid fabrics by impregnating them with single and multi-solid phase shear thickening fluids (STFs). To investigate the energy absorption capacity of Twaron 200 and Twaron 460 fabrics, surface friction, yarn tensile, and ballistic tests have been performed. Silicon carbide (SiC), graphene nanoplate (GNP), and carbon nanotube (CNT) are utilized both individually and in hybrid forms to examine the impact of multi-solid phase STFs. The research reveals that STFs reinforced with SiC and GNP exhibit higher viscosity and rheological behavior compared to other hybrid nanoparticles. The addition of SiC and GNP reinforced STF (STF/SiC + GNP) suspension significantly increases the friction coefficient by approximately 82% for Twaron 200 and 120% for Twaron 460 in comparison to neat fabric. Moreover, the maximum yarn tensile strength of Twaron 460 is higher than that of Twaron 200 in both neat and STF impregnated fabrics. The research also states that STF impregnation procedure improves the ballistic performance of neat fabrics in both fabric types. The ballistic test results show an increase in the protective performance of STF impregnated fabrics reinforced with nanoparticles. The best ballistic performance is found in STF/SiC + GNP impregnated fabrics in Twaron 200 and Twaron 460 samples.
Keywords: Shear thickening fluids; hybrid nanoparticles; ballistic test; surface friction; energy absorption performance